2016
DOI: 10.1017/s0007114516001409
|View full text |Cite
|
Sign up to set email alerts
|

Effect of BMI and fat mass on HIV disease progression in HIV-infected, antiretroviral treatment-naïve adults in Botswana

Abstract: An obesity paradox has been proposed in many conditions including HIV. Studies conducted to investigate obesity and its effect on HIV disease progression have been inconclusive and are lacking for African settings. This study investigated the relationship between overweight/obesity (BMI ≥25 kg/m2) and HIV disease progression in HIV+ asymptomatic adults not on antiretroviral treatment (ART) in Botswana over 18 months. A cohort study in asymptomatic, ART-naïve, HIV+ adults included 217 participants, 139 with BMI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…Adipokines are also associated with upregulation of pro‐inflammatory responses along with the production of other cytokines such as tumour necrosis factor α and interleukin‐6, and this can lead to different cardiometabolic complications [6]. Several studies among PLHIV have also identified a relationship between pre‐treatment BMI and not only HIV disease progression but also other non‐AIDS events, especially CVD [16,32,33]. In this study, PLHIV who were overweight and obese at ART initiation had increased hazards for developing CVD risk factors than those with normal BMI.…”
Section: Discussionmentioning
confidence: 87%
“…Adipokines are also associated with upregulation of pro‐inflammatory responses along with the production of other cytokines such as tumour necrosis factor α and interleukin‐6, and this can lead to different cardiometabolic complications [6]. Several studies among PLHIV have also identified a relationship between pre‐treatment BMI and not only HIV disease progression but also other non‐AIDS events, especially CVD [16,32,33]. In this study, PLHIV who were overweight and obese at ART initiation had increased hazards for developing CVD risk factors than those with normal BMI.…”
Section: Discussionmentioning
confidence: 87%
“…Typically, obesity can increase the risk of numerous deleterious health consequences in general populations, including hypertension, coronary artery disease, myocardial infarction, diabetes and stroke [4, 5]. In the pre-HAART era, obesity has been associated with delayed disease progression among HIV-infected patients [6, 7]. However, the effects of BMI on immune reconstitution after initiating HAART remain inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, lower BMI (18-20 kg/m 2 ) was linked to significant HIV disease progression. 20 In this study, the BMI values for all groups were within optimal range (20-23 kg/m 2 ). HIV patients have greater risk of mortality due to non-AIDS-related death which include cardiovascular diseases.…”
Section: Resultsmentioning
confidence: 46%
“…16,17 In this study, no significant differences in the body weight and BMI at baseline, three-months and six-months follow-up were observed between control and honey-supplemented groups, similar to the findings reported by Woods et al (2002) 18 and Alo et al (2014) 19 In addition, a study in Botswana found that the BMI of HIV-infected adults not on ART remained stable throughout the 18 months followup period. 20 Hence, six-month follow-up in this study may not be enough to reflect the disease progression. Another possible reason for the insignificant differences between control and honey-supplemented groups observed may be explained by relatively adequate and well-balanced diet from the prison.…”
Section: Resultsmentioning
confidence: 92%